2006
DOI: 10.1155/2006/474968
|View full text |Cite
|
Sign up to set email alerts
|

Blastomycosis in a Young African Man Presenting with a Pleural Effusion

Abstract: in a young African man presenting with a pleural effusion. Can Respir J 2006;13(8):441-444.Blastomyces dermatitidis is a dimorphic fungus endemic to northwestern Ontario, Manitoba and some parts of the United States. The fungus is also endemic to parts of Africa. Pulmonary and extrapulmonary findings of a 24-year-old African man who presented with weight loss, dry cough and chronic pneumonia not resolving with antibiotic treatment are presented. The unusual occurrence of pulmonary blastomycosis associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
(4 reference statements)
0
7
0
1
Order By: Relevance
“…A previous large systematic review on blastomycosis from 18 African countries reported a total of 81 cases, one of which was from Tanzania showing that the lack of epidemiological data does not exclude the presence of blastomycosis in Tanzania. Also, a case report from Canada reported a Tanzanian expatriate diagnosed with blastomycosis . As discussed above, in this case report, the patient had been previously treated empirically for tuberculosis before being diagnosed with blastomycosis.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A previous large systematic review on blastomycosis from 18 African countries reported a total of 81 cases, one of which was from Tanzania showing that the lack of epidemiological data does not exclude the presence of blastomycosis in Tanzania. Also, a case report from Canada reported a Tanzanian expatriate diagnosed with blastomycosis . As discussed above, in this case report, the patient had been previously treated empirically for tuberculosis before being diagnosed with blastomycosis.…”
Section: Discussionmentioning
confidence: 79%
“…Assuming that 50% of all admitted patients in Tanzania have febrile illness, we estimated 135 cases of histoplasmosis in 2012 at a rate of 0.31 per 100 000 person‐years (Table ). Apart from case reports, no reliable epidemiological data exist for IA blastomycosis, mucormycosis or fungal keratitis in Tanzania and in sub‐Saharan Africa …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, from our review of the literature, no cases of blastomycosis have been reported from Kenya or Sudan, although a few have been reported in Rwanda, Tanzania, and Uganda. [11][12][13] This case underscores the need to maintain a high index of suspicion for B. dermatitidis in patients with vertebral osteomyelitis and paravertebral fluid collections, particularly since vertebral tuberculosis can manifest similarly. In this case, despite the patient's exposure to an area hyperendemic for blastomycosis, the correct diagnosis was made only after there was progression of signs and symptoms while on antituberculous therapy.…”
Section: Erratamentioning
confidence: 83%
“…Blastomyces dermatitidis , including the more recently described cryptic species B. gilchristi (together referred to herein as B. dermatitidis species complex), and B. helicus cause disease in humans and animals via inhalation of airborne spores [ 6 , 14 , 164 171 ]. The mycelial form of the fungus primarily dwells in wooded land with damp soil near lakes, waterways and rivers [ 164 , 167 , 171 175 ]. Excavation and construction in endemic areas have been identified as risk factors for disease acquisition [ 176 ].…”
Section: Methodsmentioning
confidence: 99%
“…Excavation and construction in endemic areas have been identified as risk factors for disease acquisition [ 176 ]. B. dermatitidis species complex is endemic in the mid-west, southeast, east and south-central USA; northwest Ontario, Quebec, Manitoba and Saskatchewan in Canada; central, eastern and southern Africa; and India [ 6 , 7 , 28 , 164 , 166 , 167 , 177 – 185 ]. Figure 3 shows the geographic distribution of B. dermatitidis species complex worldwide.…”
Section: Methodsmentioning
confidence: 99%